WSRF−Based Modeling of Clinical Trial Information for Collaborative Cancer Research - Zang, T; Calinescu, R; Harris, S; Tsui, A; Kwiatkowska, M; Gibbons, J; Davies, J; Maccallum, P; Caldas, C (2008)
The CancerGrid consortium is developing open-standards cancer informatics to address the challenges posed by modern cancer clinical trials. This paper presents the service-oriented software paradigm implemented in CancerGrid to derive clinical trial information management systems for collaborative cancer research across multiple institutions. Our proposal is founded on a combination of a clinical trial (meta)model and WSRF (Web Services Resource Framework), and is currently being evaluated for use in early phase trials. Although primarily targeted at cancer research, our approach is readily applicable to other areas for which a similar information model is available.